Impacts of the 2019 pandemic of severe acute respiratory syndrome–coronavirus 2 on the quality of life of patients with inflammatory rheumatic diseases: Vpliv epidemije SARS-CoV-2 na kvaliteto življenja bolnikov z vnetnimi revmatskimi boleznimi - Lah, Domen; Holc, Iztok (Acta Medico-Biotechnica, 2023)
Purpose: The aim of this study was to assess the impact of the SARS-CoV-2 pandemic and protective measures on the QoL of patients with inflammatory rheumatic diseases (IRDs) who received treatment at the Department of Rheumatology at the University Medical Centre Maribor (UCM-MB).Methods: A questionnaire was sent to IRD patients who visited a rheumatology outpatient clinic or were contacted by phone or virtually at least once between February 1, 2020 and May 30, 2021. The questionnaires were included if returned to UCM-MB by January 1, 2022 and were completed correctly and in full.Results: Of the 125 patients who met the inclusion criteria, 57 (45.6%) had no cancelled rheumatology appointments, 52 (41.6%) had one, 15 (12.0%) had two, and one patient (0.8%) had three. The most preferred mode of communication was in-person meetings with a rheumatologist (89%) and the least was a video call (1%). Only 2% of patients had problems obtaining medication during the pandemic, but none reported consequences with disease status. More than half (58%) of patients agreed with the restrictions during the pandemic and 5% stated the restrictions should be terminated. Most (70%) patients were vaccinated against SARS-CoV-2 and 21% reported SARS-CoV-2 infection. The mean disease activity score (DAS-28) was 3.100 ± 1.292 (rheumatoid arthritis, 3.252 ± 1.209; psoriatic arthritis, 2.927 ± 1.376; p = 0.274; t = 1.101).Conclusion: The pandemic and associated protective measures had deleterious effects on the QoL of IRD patients.
Keywords: severe acute respiratory syndrome–coronavirus 2, rheumatic diseases, quality of life, pandemic, telemedicine